Comparison of intrathecal isobaric ropivacaine plus dexmedetomidine and isobaric ropivacaine plus clonidine for elective lower abdominal and lower limb surgeries - Umamaheshwara Rao W; Reddy, Lakshma; Joshi, Sachin D (Academia Anesthesiologica International, 2016)
Aim: To compare intrathecal isobaric ropivacaine plus dexmedetomidine and isobaric ropivacaine plus clonidine for elective lower abdominal and lower limb surgeries. Methodology: Eighty patients undergoing lower abdominal and lower limb surgeries under intrathecal anesthesia of either gender were randomly divided into 2 groups of 40 each. Group I patients (male- 22, female-18) received isobaric ropivacaine 0.75% 15 mg + 30 mcg clonidine and Group II patients (male- 24, female-16) received isobaric ropivacaine 0.75% 15 mg + 10 mcg dexmedetomidine. Parameters such as sensory blockade, motor blockage, analgesia and VAS was recorded. Results: The mean duration of surgery in group I was 106.4 minutes and in group II was 112.8 minutes. The mean time to onset of sensory analgesia was 6.8 minutes in group I and 4.0 minutes in group II. The mean time taken to achieve complete motor blockade was 14.2 minutes in group I and 13.4 minutes in group II. The time taken for regression of sensory block to T-12 level was 154.2 minutes in group I and 196.5 minutes in group II. The mean time to first postoperative analgesic requirement was 262.8 minutes in group I and 342.6 minutes in group II. The difference was significant (P< 0.05). The mean VAS in group I was 4.8 and in group II was 3.6. The difference in both groups was significant (P< 0.05). Conclusion: Dexmedetomidine with ropivacaine showed earlier sensory blockade, prolonged duration of sensory and motor blockade for lower limb surgeries.